STRATEGI KOMUNIKASI PEMERINTAH DALAM MENINGKATKAN TRANSPARANSI KEUANGAN DESA WADAS KABUPATEN KARAWANG - , Siti Hafsyah Chaniago; Hanny Purnamasari; Rachmat Ramdani (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The existence of regulations in Law no. 6 of 2014 concerning the implementation of village government has provided a legal umbrella for the community to obtain public information, but in practice, village governments often face obstacles in fulfilling these rights. Lack of human resource capacity and limited available technology are some of the factors that hinder the realization of transparency in village government management. This study aims to determine the strategy of the Wadas Village government in conveying information about financial reports using Lasswell's communication theory which contains five elements of the communication process, namely communicators, messages, media, recipients/communicants and effects/feedback. The method used in this study is descriptive qualitative research with interview, observation and documentation data collection techniques. The results of this research indicate that all Wadas Village officials can act as communicators in conveying messages of Information about Village Income and Village Expenditure Information. The delivery of information messages is carried out through the Siskeudes media, Village Social Media, Musrenbangdes, APBDes Billboards, Village Simple. While the Wadas Village Community, BPD and Village Inspectorate are the communicants. However, from several strategies implemented, there was a lack of feedback provided by the community through various media used by Wadas Village